1992
DOI: 10.1007/bf01928178
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplets of neuroepithelial cells are a major calcium storage site during neural tube formation in chick and mouse embryos

Abstract: In situ precipitation of calcium (Ca2+) with fluoride and antimonate shows that Ca(2+)-specific precipitate is localized almost exclusively within lipid droplets of neuroepithelial cells during neural tube formation in chick and mouse embryos. The density of Ca2+ precipitate within lipid droplets is generally greater in the apical ends of cells situated in regions of the neuroepithelium that are actively engaged in bending. These findings suggest that lipid droplets, in addition to providing a source of metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In the present study, accumulation of Ca 2+ by LD, probably in the polar heads of the phopholipid layer surrounding the LD or in lipid droplet-associated proteins, may have indirect beneficial effects by reducing the detrimental consequences of cytosolic Ca 2+ overload during the first minutes of reperfusion. Previous studies on neuroepithelial cells showed that LD also serve as Ca 2+ -storage and -releasing sites (Bush et al 1992), further supporting the idea of LD being able to buffer cytosolic Ca 2+ during simulated ischaemia-reperfusion.…”
Section: Mechanism Of Protectionsupporting
confidence: 58%
“…In the present study, accumulation of Ca 2+ by LD, probably in the polar heads of the phopholipid layer surrounding the LD or in lipid droplet-associated proteins, may have indirect beneficial effects by reducing the detrimental consequences of cytosolic Ca 2+ overload during the first minutes of reperfusion. Previous studies on neuroepithelial cells showed that LD also serve as Ca 2+ -storage and -releasing sites (Bush et al 1992), further supporting the idea of LD being able to buffer cytosolic Ca 2+ during simulated ischaemia-reperfusion.…”
Section: Mechanism Of Protectionsupporting
confidence: 58%
“…Lipid droplets (LDs) are primary fatty acid depots for mitochondrial FAO (Gross and Silver, 2014), and these structures are found in embryonic NSCs (Bush et al, 1992; Saito et al, 2009). To test whether interfering with fatty acid mobilization from LDs recapitulates the NSC derangements induced by direct compromise of mitochondrial FAO, a dominant-negative interference assay was developed.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we chose Nile red, which is a frequently used probe for assessment of lipids and lipid droplets; note that it also shows Ca 2+ -sensitivity, for example, by detecting conformational changes of calmodulin upon binding Ca 2+ or by binding phospholipid/Ca 2+ complexes. In the presence of lipids and other amphiphilic molecules, Nile red displays both spectral (green/orange) and fluorescence lifetime changes. We tested if the green fluorescence of Nile red could potentially interfere with Lgr5-GFP signals (Figure C,D).…”
Section: Resultsmentioning
confidence: 99%
“…16 Potentially, the observed changes in lipid droplets and cytoplasmic fractions of Nile red were caused by Ca 2+ binding to the lipid droplets and cellular membranes, which could act as additional depots in cells of the intestinal epithelium, similar to cardiomyocytes and neuroepithelial and immune cells. 60,61,67 If this is the case, lipid droplets can play a role in rapid restoration and maintenance of the external Ca 2+ pool.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation